(untitled) (International journal of medical sciences, 2026)
Thymus vulgaris L. (common thyme) demonstrates exceptional adaptability as a perennial evergreen subshrub in the Fergana Valley's arid continental climate. This study analyzes its growth dynamics, including March-April seed sowing with 25-30 day germination periods, seasonal requirements of 8-9 irrigations, and high tolerance to both drought and cold temperatures down to -15°C. Optimal plant densities range from 111,000-222,000 plants/ha on well-drained neutral soils (pH 6.0-8.0), yielding 2-4 t/ha of harvestable aerial biomass rich in thymol (40-60%) and carvacrol (10-20%). Harvesting occurs from late April to May, capitalizing on the region's hot summers that enhance essential oil synthesis. The plant's ethnobotanical significance in Fergana and Andijan traditional medicine underscores its economic potential for pharmaceutical, cosmetic, and food industries.